2014
DOI: 10.3390/ijms150917115
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Ameliorates Depressive Comorbidity in ADHD Children without any Modification on Differences in Serum Melatonin Concentration between ADHD Subtypes

Abstract: The vast majority of Attention-deficit/hyperactivity disorder (ADHD) patients have other associated pathologies, with depressive symptoms as one of the most prevalent. Among the mediators that may participate in ADHD, melatonin is thought to regulate circadian rhythms, neurological function and stress response. To determine (1) the serum baseline daily variations and nocturnal excretion of melatonin in ADHD subtypes and (2) the effect of chronic administration of methylphenidate, as well as the effects on symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…More than 60% of adults with ADHD reported increased sleepiness during day time ( 54 , 55 , 70 ). Delayed timing of melatonin secretion is systematically found in children and adults with ADHD ( 54 , 55 , 71 ). Rybak et al suggested that a substantial circadian phase delay considerably impacts the core pathology of the ADHD ( 72 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 60% of adults with ADHD reported increased sleepiness during day time ( 54 , 55 , 70 ). Delayed timing of melatonin secretion is systematically found in children and adults with ADHD ( 54 , 55 , 71 ). Rybak et al suggested that a substantial circadian phase delay considerably impacts the core pathology of the ADHD ( 72 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reported alterations in amino acid metabolism can be characterized by changes in tryptophan/kynurenine metabolism, which representatively showed an increase of 3-hydroxykynurenine concentrations in the plasma of ADHD patients [ 17 , 18 , 19 , 40 ]. On the other hand, melatonin metabolism, monoamine metabolism and glutamate metabolism pathways are also repeatedly investigated in the brain or urine of ADHD patients [ 20 , 23 , 41 , 42 , 43 , 44 , 45 , 46 ]. In this study, in order to investigate the metabolite changes involved in the neuropathology of ADHD-like hyperactivity induced by PAE and the ameliorative effects of HX106 treatment, we performed untargeted metabolomics using GC-TOF-MS. We clearly presented that the metabolite profiles in plasma, liver, colon and feces were altered in the OPAE group and that the changed direction was reversed by the HX106 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned events lead to decreased synaptogenesis and decreased neuronal network formation and function causing learning and memory deficit at patients have other associated pathologies, with depressive symptoms as one of the most prevalent. Among the mediators that may participate in ADHD, melatonin is thought to regulate circadian rhythms, neurological function and stress response Cubero-Millán et al [14]. In addition to, system-level, local and cross-regional interactions, a consolidation mechanism involves stabilization of memory representations at the synaptic level.…”
Section: Discussionmentioning
confidence: 99%